1999
DOI: 10.1105/tpc.11.9.1769
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposon BARE-1 and Its Role in Genome Evolution in the Genus Hordeum

Abstract: The replicative retrotransposon life cycle offers the potential for explosive increases in copy number and consequent inflation of genome size. The BARE-1 retrotransposon family of barley is conserved, disperse, and transcriptionally active. To assess the role of BARE-1 in genome evolution, we determined the copy number of its integrase, its reverse transcriptase, and its long terminal repeat (LTR) domains throughout the genus Hordeum . On average, BARE-1 contributes 13.7 ϫ 10 3 full-length copies, amounting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
167
3
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(187 citation statements)
references
References 76 publications
15
167
3
2
Order By: Relevance
“…The increased frequency of ESTs similar to retrotransposons in cDNA libraries from stressed plants also parallels similar results based on experimental evidence (Kumar and Bennetzen 1999;Vicient et al 1999) and suggests that the observed frequencies are the result of a particular transcription pattern rather than an artifact produced by genomic contamination of the cDNA libraries.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The increased frequency of ESTs similar to retrotransposons in cDNA libraries from stressed plants also parallels similar results based on experimental evidence (Kumar and Bennetzen 1999;Vicient et al 1999) and suggests that the observed frequencies are the result of a particular transcription pattern rather than an artifact produced by genomic contamination of the cDNA libraries.…”
Section: Resultssupporting
confidence: 84%
“…Ty1-copia-type and Ty3-gypsy-type retroelements are two abundant classes of retrotransposons in the Triticeae genomes (Suoniemi et al 1996a;Gribbon et al 1999;Vicient et al 1999), comprising approximately 35% of the rye genome (Pearce et al 1997) and a minimum of 20% of the wheat genome (Lagudah et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently occurring element from hybridization data was also Huck (Table 2), which identified most of the BAC clones that contained other dispersed repeats. The high frequency observed for Huck relative to the proportion estimated from sequence data may result from a higher frequency of solo LTRs than intact elements, as has been recently demonstrated for the BARE-1 element in barley (Vicient et al 1999;Shirasu et al 2000). In the case of Prem-1, the sequence abundance was definitely underestimated as it was derived only from homology to the LTRs, as the internal domain of the element has not been described.…”
Section: Hybridization To Bac Clones Determines Abundance and Distribmentioning
confidence: 80%
“…The copy number given here for Huck reflects the number of LTRs, so the number of entire elements should be exactly half. Excessive numbers of LTRs, however, may be a feature of complex plant genomes (Vicient et al 1999) and 85% of the LTRretrotransposons found in humans consist only of an isolated LTR (International Human Genome Sequencing Consortium 2001). Overall, the amplification of these retroelements in the Zea species may predate the most recent common ancestor because the same elements have successfully invaded all of these genomes to a similar extent.…”
Section: Maize Repetitive Elementsmentioning
confidence: 99%
“…Along with polyploidization, accumulation of repetitive DNA, particularly long terminal repeat retrotransposons (LTR-RTs), is the primary mechanism driving plant genome expansion . In large-genome species such as maize, barley, and wheat, LTR-RTs make up more than 60%-80% of their genomes, and the majority of these elements have amplified within the last few million years (SanMiguel et al 1996(SanMiguel et al , 1998Vicient et al 1999;Wicker et al 2001;Bruggmann et al 2006). A particularly striking study shows that Oryza australiensis, a wild species of rice, has accumulated more than 90,000 copies of LTR-RTs during the last three million years, leading to a twofold increase in genome size without polyploidization (Piegu et al 2006).…”
mentioning
confidence: 99%